Copyright Reform in South Africa: Two Joint Academic Opinions on the Copyright Amendment Bill [B13B 2017] - Beiter, Klaus D; Fiil-Flynn , Sean M.; Forere , Malebakeng; Klaaren, Jonathan; Ncube, Caroline; Nwauche, Enyinna; Rens, Andrew; Samtani, Sanya; Schonwetter, Tobias (Potchefstroom Electronic Law Journal, 2022)
South Africa is in the process of reforming its copyright law, attempting to update and align it with constitutional rights and existing and prospective international treaty obligations. With the adoption of the Copyright Amendment Bill [B13B-2017] by both Houses of Parliament in March 2019, the apartheid-era Copyright Act of 1978 had almost successfully been amended, when the President of the Republic withheld his assent to the Bill referring it back to Parliament citing reservations about its constitutionality. Following calls for public comment by the parliamentary Portfolio Committee on Trade and Industry on the President’s reservations, a coalition of copyright and constitutional law experts, convinced of the constitutionality of the Bill, submitted two legal opinions to the Committee. The two opinions presented in this contribution underline the importance of copyright reform, as envisaged in the Bill, to bringing South African copyright law into the digital age and realising several constitutional rights including the rights to education, cultural participation, language, freedom of expression, and access to knowledge of everyone, without discrimination.